Strategic plan for Roadway Grill Corporation - Jadraque, Angelo E. (School of Management, University of the Philippines Mindanao, 2008)
The restaurant industry specifically in Davao City is becoming more dynamic in its different aspects like competition that is getting stronger among business players. Strategic options and implementation plans for a five-year period are contained in this paper for the company. This aims to address different issues in the restaurant industry that are affecting every industry player like Roadway Grill Corporation. The key issues that this paper tried to address are the weak competitive position of the company, the slow response by the management to different challenges in the market, and the low level of revenue and income generation. In coming up with the strategic options, thorough analyses on the external and internal environments of the enterprise were done utilizing pertinent data gathered from reliable sources. Data gathered were validated and examined to check their relevance to the analysis. Using different tools in the analyses helped in coming up with the strategic options that the company can implement in its business operations. Strategic options were evaluated as to their relevance and attractiveness in addressing the different issues in the industry. Contents of this paper will help the company to set a clear direction of its business. Strategies are associated to the long-term objectives as stated impliedly in its vision and mission statements. Moreover, implementing programs are provided with the short-term objectives to give a certain level of confidence for attaining success upon implementation. Control measures and tools will help the management in monitoring the different phases of implementation. Within this five-year plan, implementation of strategic options could be subjected to any changes in the industry that are non-controllable and not covered by the scope of this paper. In such event, implementation plans would be modified to address the encountered uncontrollable conditions in order for the business to remain focus for the attainment of business objectives for the five-year period and beyond.